When abortion was a crime : women, medicine, and law in the United States, 1867-1973 - Reagan, Leslie J. (University of California Press, 1997)
As we approach the 30th anniversary of Roe v. Wade, it's crucial to look back to the time when abortion was illegal. Leslie Reagan traces the practice and policing of abortion, which although illegal was nonetheless widely available, but always with threats for both doctor and patient. In a time when many young women don't even know that there was a period when abortion was a crime, this work offers chilling and vital lessons of importance to everyone. The linking of the words "abortion" and "crime" emphasizes the difficult and painful history that is the focus of Leslie J. Reagan's important b.